Genetic determination of plasma lipids and insulin in the Czech population - Hubacek, J A; Waterworth, D M; Poledne, R; Pitha, J; Skodová, Z; Humphries, S E; Talmud, P J (Clinical biochemistry, 2001)
OBJECTIVES: To evaluate the association between plasma lipids and insulin and variation in the genes for apolipoproteins (APO) E (CfoI), B (insertion/deletion), C1 (HpaI), and C3 (C-482T, C3238G) in a population-based Czech Slavonic study. DESIGN AND METHODS: In 131 men and 154 women, polymorphisms were investigated using PCR. In the same subjects plasma lipid levels and insulin were measured. RESULTS: In the women, carriers of the e4 allele had higher apoB (p = 0.03) and triglyceride (p = 0.03) compared to e3 homozygotes, whereas in the men, the effect of the e4 allele was seen on total cholesterol (p = 0.02), LDL cholesterol (p = 0.003) and apoB (p = 0.001). Compared with SP27 (insertion) homozygotes of the APOB polymorphism, women SP24 (deletion) homozygotes had higher levels of total (p = 0.003) and LDL cholesterol (p = 0.007) and apoB (p = 0.05). No significant effect was seen in the men. Women homozygous for the APOC3 -482T allele had higher insulin levels than -482C homozygotes (p = 0.03). Men homozygous for APOC3 -482T allele have the highest plasma triglyceride level (p = 0.02). The APOC1 polymorphism exhibited no significant effect on any of the parameters studied. CONCLUSIONS: In this sample, variation at the APOE, APOB and APOC3 genes play a role in determining plasma levels of insulin and lipids, and emphasize the importance of gender-associated effects in the genetic determinations.
Keywords: mutace; Apolipoproteins C; dospělí; apolipoproteiny E; cholesterol; Female; Genotype; LDL-cholesterol; polymerázová řetězová reakce; Adult; homozygot; Cholesterol, LDL; ženské pohlaví; Polymerase Chain Reaction; triglyceridy; lipidy; apolipoprotein C-III; Triglycerides; lidé; apolipoprotein C-I; genotyp; Mutation; Insulin; Apolipoproteins B; Lipids; Homozygote; apolipoproteiny C; Cholesterol; Genetic Variation; Humans; Sex Factors; Apolipoprotein C-I; Male; Apolipoproteins E; sexuální faktory; Czech Republic; polymorfismus genetický; HDL-cholesterol; apolipoproteiny B; alely; Česká republika; Alleles; Apolipoprotein C-III; lidé středního věku; mužské pohlaví; genetická variace; inzulin; Polymorphism, Genetic; Middle Aged; Cholesterol, HDL